Towards sustainable forestry development in Patagonia: truths and myths of environmental impacts of plantations with fast-growing conifers - Gyenge, Javier; Fernandez, María Elena; Rusch, Veronica Elena; Sarasola, Mauro Miguel; Schlichter, Tomas Miguel (2017)
In NW Patagonia region, Argentina, South-America, there are about 70,000 ha of planted forests replacing from native forests to grasslands with different degrees of deterioration due to previous land use. Although forestry development has been quite slow in this region compared to other regions of the country, it is expected that this activity will be increasing in the future due to provincial and national government policies of forestry incentives. In general, only scarce information is available about the environmental impact of forestation in the region. Our objective was to bring together the knowledge about the changes in biodiversity, water cycle and water resources, soil characteristics and the risk of invasion of introduced exotic fast-growing coniferous species on native ecosystems. The analyses revealed that the greatest changes in biodiversity, water consumption and invasion risk occurred when the introduction of trees was in grasslands compared to forest or shrublands. However, from our results we can conclude that, at the current developmental stage of forestry activity in Patagonia, the negative environmental impact is very low or even nil, with the positive impacts –economic and socialpossibly being higher and leading to a more positive balance as a whole. However, we recognize that potential negative impacts, whose magnitude will depend on several aspects discussed in the paper, could increase in the future in relation to the expansion of the forested areas. With the available information we can then formulate prescriptions and management strategies for exotic systems, in order to guarantee the long term sustainability of the activity. In this regard, we have the opportunity of developing a sustainable production activity from the very beginning.